1983
DOI: 10.1161/01.hyp.5.5.712
|View full text |Cite
|
Sign up to set email alerts
|

Regional vascular capacitance in rabbit one-kidney, one clip hypertension.

Abstract: SUMMARY One-kidney Goldblatt hypertensive rabbits (New Zealand White) were studied after durations of renal artery clipping that varied from 6 to 17 days. Measurements included arterial pressure (ABP), iliac venous pressure (IVP), left atrial pressure (LAP), cardiac output (CO) (by thermodilution), blood volume (BV), cardiopulmonary volume (CPV), and hind leg thermodilution volume (HLV). These were determined at steady-state as well as during acute blood volume expansion. In sham-clipped animals, ABP was 74 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Very similar results (i.e. increased central but not total blood volumes) have been reported in experimental hypertension in animals44, 45. Thus, redistribution of circulating blood without a change in its total volume could be an important aspect of the hemodynamics of hypertension.…”
Section: Vascular Capacitance and Hypertensionsupporting
confidence: 77%
“…Very similar results (i.e. increased central but not total blood volumes) have been reported in experimental hypertension in animals44, 45. Thus, redistribution of circulating blood without a change in its total volume could be an important aspect of the hemodynamics of hypertension.…”
Section: Vascular Capacitance and Hypertensionsupporting
confidence: 77%
“…It has been reported that venous compliance is decreased and venous contractility is enhanced in human essential hypertension (10)(11)(12) and also in experimental hypertensive animals (13)(14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%